2006
DOI: 10.1021/jp0650073
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the CN + HCNO Reaction

Abstract: The kinetics of the CN + HCNO reaction were studied using laser-induced fluorescence and infrared diode laser absorption spectroscopy. The total rate constant was measured to be k(T) = (3.95 +/- 0.53) x 10(-11) exp[(287.1 +/- 44.5)/T] cm3 molec(-1) s(-1), over the temperature range 298-388 K, with a value of k1 = (1.04 +/- 0.1) x 10(-10) cm3 molec(-1) s(-1) at 298 K. After detection of products and consideration of secondary chemistry, we conclude that NO + HCCN is the only major product channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…No experimental data has previously been reported for these reactions. We obtained upper limits for the 298 K rate constants of reactions 10−13 using standard pseudofirst order kinetics techniques, similar to our previous reports of the kinetics of HCNO with OH, 11 CN, 12 and NCO 13 radicals. For the NH + HCNO reaction, we used laser induced fluorescence (LIF) at 336 nm to monitor the decay of NH radicals produced by 266 nm Nd:YAG laser photolysis of HN 3 precursor molecules.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…No experimental data has previously been reported for these reactions. We obtained upper limits for the 298 K rate constants of reactions 10−13 using standard pseudofirst order kinetics techniques, similar to our previous reports of the kinetics of HCNO with OH, 11 CN, 12 and NCO 13 radicals. For the NH + HCNO reaction, we used laser induced fluorescence (LIF) at 336 nm to monitor the decay of NH radicals produced by 266 nm Nd:YAG laser photolysis of HN 3 precursor molecules.…”
Section: Resultssupporting
confidence: 67%
“…Many product channels are thermodynamically possible: Thermochemical information has been obtained from standard tables 24 as well as other literature for the heats of formation of HCNO, NCO, 25 HCNN, 26 HCCO, 27 NCCO, 28 and CCO. 29 In our previous experiment, 12 we detected NO products, presumably from channel 1a, and upon the addition of NO reagent, we detected CO, CO 2 , and N 2 O secondary products, which we attributed to the following secondary chemistry:…”
Section: Introductionmentioning
confidence: 55%
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 70%
“…HCNO (fulminic acid) is the less stable isomer of isocyanic acid; the kinetics of several reactions involving HCNO has only recently been studied [3][4][5][6][7]. There is only one previous study of the photochemistry of HCNO, an infrared laser spectroscopic study from our laboratory that identified five separate photolysis channels in the 248 nm photodissociation of this molecule [8].…”
Section: Introductionmentioning
confidence: 99%